Ekspresi Glukosa Transporter-2 di Sel Beta Pankreas dan Sel Hepatosit Tikus yang Diinduksi Diabetes Mellitus - teodhora teodhora (Brawijaya University, 2021)
Diabetes Mellitus (DM) is an incurable disease that can be prevented clinically from worsening. This disease is based on classification related to pancreatic damage in total or partial so that the impact on insulin production. Glucose transporter is a protein that can glucose uptake from outside cell into cell and provides an important role in the body's glucose homeostasis. Glucose transporter-2 (GLUT-2) is found in the pancreas, liver, and kidney. Parameters used are the expression and amount of GLUT-2 density in pancreatic Î² cells and in hepatocyte cells in normal and diabetic Rat. Used Wistar strain male white rats. An immunohistochemistry (IHC) staining technique was performed to observe the expression of GLUT-2 and the macbiophotonics image J program to determine total density of GLUT-2. GLUT-2 is marked in brown in the cell nucleus surrounded by cytoplasm. The results showed an increased in GLUT-2 expression in hepatocyte cells with a total density of 25,447,052 and a decreased in GLUT-2 expression in pancreatic Î² cells with a total density of 5,074,544 by Streptozotocin 50 mg/kg BB-Nicotinamide 100 mg/kg BB (STZ-NA) Intraperitonial routes in induced DM rat. STZ-NA induced triggers damage in pancreatic Î² cells and significantly influences the expression of GLUT-2 protein. High blood glucose levels give different GLUT-2 activity in hepatocyte cells due to the effects of induced agent.